AN ANALYSIS OF FIRST LANGUAGE ACQUISITION IN CHILDREN - Masykur (Universitas Wiralodra, 2017)
The current study investigates the accessibility of a systematic pattern to children learning their first language, and also it is a try to show the effect of the quantity of input on first language acquisition. To these aims, two case studies were carried out on six children learning as their first language. The participants of the first study were three children acquiring their first language in Indramayu being followed for 12 months (24-36 months) to see if they all passed the same pattern in language development. The participants of the second study were three Children (who were exposed to less input) acquiring their first language in Indramayu being followed for 12 months (24-36 months) to see if the language development was affected considering the amount of input they were exposed to. In-depth interviews, observations, audio and video recordings, notes and reports were used to collect the data for this study. The data collected for each Children was analyzed separately, and the stages of development were reported for each children accordingly. The findings support the claim that the process of language acquisition depends on an innate language ability which holds that at least some linguistic knowledge exists in humans at birth, and also the input that learners receive plays a very important role in the language acquisition since the input activates this innate structure.